Long-term motor, cognitive and behavioral outcome of acute disseminated encephalomyelitis. (May 2016) - Shilo, Smadar; Michaeli, Orli; Shahar, Eli; Ravid, Sarit
Abstract: Objective: The purpose of this study was to evaluate the long-term motor and neurocognitive outcome of children with acute disseminated encephalomyelitis and to identify prognostic risk factors. Methods: The study included 43 children who were hospitalized due to acute disseminated encephalomyelitis during the years 2002–2012. The children underwent full neurological examinations, along with comprehensive neurocognitive and behavioral assessments. Results: Twenty-six (61%) children had different degrees of neurological sequelae after a mean follow-up of 5.5 ± 3.5 years. The most common residual impairment included attention-deficit hyperactivity disorder (44%), behavioral problems (32%), and learning disabilities (21%). Five (12%) children had a full-scale IQ of 70 or less, compared to 2.2% in the general population. Conclusions: Neurocognitive sequelae were found even in children who were considered as fully recovered at the time of discharge. Risk factors for severe neurological sequelae were older age at diagnosis and male gender. We suggest neuropsychological testing and long-term follow-up for all children with acute disseminated encephalomyelitis, even in the absence of neurological deficits at discharge. Highlights: Attention deficit disorder is common after childhood ADEM. Behavioral and learning disabilities are common after childhood ADEM. Even children who were considered fully recovered may be significantly affected. Male gender and older age at diagnosis are risk factors for poor outcome.